Chromone derivatives and other constituents from cultures of the marine sponge-associated fungus penicillium erubescens KUFA0220 and their antibacterial activity - Kumla D. (2018)
A previously unreported chromene derivative, 1-hydroxy-12-methoxycitromycin (1c), and four previously undescribed chromone derivatives, including pyanochromone (3b), spirofuranochromone (4), 7-hydroxy-6-methoxy-4-oxo-3-[(1E)-3-oxobut-1-en-1-yl]-4H-chromene-5-carboxylic acid (5), a pyranochromone dimer (6) were isolated, together with thirteen known compounds: β-sitostenone, ergosterol 5,8-endoperoxide, citromycin (1a), 12-methoxycitromycin (1b), myxotrichin D (1d), 12-methoxycitromycetin (1e), anhydrofulvic acid (2a), myxotrichin C (2b), penialidin D (2c), penialidin F (3a), SPF-3059-30 (7), GKK1032B (8) and secalonic acid A (9), from cultures of the marine sponge- associated fungus Penicillium erubescens KUFA0220. Compounds 1a-e, 2a, 3a, 4, 7-9, were tested for their antibacterial activity against Gram-positive and Gram-negative reference and multidrug-resistant strains isolated from the environment. Only 8 exhibited an in vitro growth inhibition of all Gram-positive bacteria whereas 9 showed growth inhibition of methicillin-resistant Staphyllococus aureus (MRSA). None of the compounds were active against Gram-negative bacteria tested. © 2018 MDPI. All Rights Reserved.